PELAKSANAAN PERJANJIAN JUAL BELI TANDAN BUAH SEGAR KELAPA SAWIT ANTARA PT. SAWIT ASAHAN INDAH DENGAN SUPPLIER TBS EXTERNAL UD RIDHO MANDIRI - Luthfi Syasnur Fadjar; Maryati Bachtiar; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Cooperation is an agreement where a person first binds himself with another party according to the will of each of the parties, in which the agreement is valid as a law to both parties. In accordance with Article 1338 of the Civil Code paragraph (1), namely all agreements made legally is valid as law for those who make them. UD Ridho Mandiri and PT Sawit Asahan Indah are companies engaged in oil palm plantations that manufactures crude palm oil into oil to be marketed to the community and used as daily necessities. This research focuses on the sale and purchase agreement between PT Sawit Asahan Indah and UD Ridho Mandiri's external supplier partnership. The purpose of writing this thesis, namely: to find out the implementation of the FFB sale and purchase agreement between UD Ridho Mandiri and UD Ridho Mandiri, to find out the obstacles faced in the implementation of the sale and purchase agreement between UD Ridho Mandiri and PT Sawit Asahan Indah, and to define the legal consequences occurred in the implementation of the sale and purchase agreement between UD Ridho Mandiri and PT Sawit Asahan Indah. This research is conducted with sociological legal research methods by conducting legal identification of the effectiveness of the appilcation of law enforcement in society.From the research results, there are three main things that can be concluded: first, the implementation of the agreement between PT Sawit Asahan Indah and UD Ridho Mandiri, in which PT Sawit Asahan Indah comitted a wrongdoing (wanprestasi) against UD Ridho Mandiri.Second, the constraints faced in the implementation of the agreement, caused by flood and COVID-19. Third, the legal consequences of the wrongdoing comitted by PT Sawit Asahan Indah in thesale and purchase agreement with UD Ridho Mandiri.The author's suggestion in this research is that PT Sawit Asahan Indah as the first party must fulfill the agreement in the form of debt repayment to UD Ridho Mandiri as the second party. This is done in order to achieve the main purpose of making an agreement, where the agreement must be mutually beneficial to the parties. There needs to be self-awareness by the first party in order to carry out its good faith as soon as possible. With this good faith and honesty, it can make a problem that starts off complicated become a little lighter.Keywords: Agreement – Trade–Cooperation